1999
DOI: 10.1046/j.1469-7580.1999.19540491.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation in great ape and modern human mandibles

Abstract: Adult mandibles of 317 modern humans and 91 great apes were selected that showed no pathology. Adult mandibles of Pan troglodytes troglodytes, Pongo pygmaeus pygmaeus and Gorilla gorilla gorilla and from 2 modern human populations (Zulu and Europeans from Spitalfields) were reliably sexed. Thirteen measurements were defined and included mandibular height, length and breadth in representative positions. Univariate statistical techniques and multivariate (principal component analysis and discriminant ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
149
3
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(186 citation statements)
references
References 22 publications
26
149
3
6
Order By: Relevance
“…While some scholars argue that the mandible is of not much value in identifying recent human populations (e.g. Humphrey et al, 1999), other recent studies have pointed out that actually, the mandible can reflect population history quite well, as inferred from geographical distance between populations (Nicholson and Harvati, 2006;Harvati and Weaver, 2006), but also from "population continuity" (Galland et al, 2016;Šešelj et al, 2015). Geographical distance might be a fairly robust proxy for inferring restricted gene flow between populations and a good estimate of different climatic conditions.…”
Section: Homo -Journal Of Comparative Human Biology 68 (2017) 329-342mentioning
confidence: 99%
“…While some scholars argue that the mandible is of not much value in identifying recent human populations (e.g. Humphrey et al, 1999), other recent studies have pointed out that actually, the mandible can reflect population history quite well, as inferred from geographical distance between populations (Nicholson and Harvati, 2006;Harvati and Weaver, 2006), but also from "population continuity" (Galland et al, 2016;Šešelj et al, 2015). Geographical distance might be a fairly robust proxy for inferring restricted gene flow between populations and a good estimate of different climatic conditions.…”
Section: Homo -Journal Of Comparative Human Biology 68 (2017) 329-342mentioning
confidence: 99%
“…One of the most obvious alternative models is that agricultural populations will experience different biomechanical or selective pressures on mandibular shape than hunter-gatherers, such that modifications have occurred either via phenotypic plasticity or natural selection. Previous morphometric studies (23,24) found some geographical patterning in mandibular morphology, as well as a signal of climatic and/or masticatory plasticity. However, hunter-gatherer and agricultural populations have never explicitly been compared at a global level to evaluate the likely role of subsistence economy in the evolution of the mandible.…”
mentioning
confidence: 99%
“…Geographically two of the most variable measurements are the height (superoinferiorly) and the width (anteriorposteriorly) of the ascending ramus. 3 Dental nerve blocks are based on anatomic norms and statistical averages of nerve pathways and bone structure. Any variation from the 'average patient' can result in failed anaesthesia, as suggested in our case study.…”
Section: Discussionmentioning
confidence: 99%